Method for producing granules for use in electrodes of all-solid-state batteries and electrodes for all-solid-state batteries

By coating conductive materials on active materials and spraying binders with controlled stirring, the method addresses binder migration issues, improving porosity and electrolyte penetration in all-solid batteries, thereby enhancing battery performance.

JP2025502845APending Publication Date: 2025-01-28LG ENERGY SOLUTION LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024539985
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-03-16
Filing Date
2023-03-17
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the production of all-solid batteries, the movement of binders to the exterior of granular particles during drying leads to reduced porosity, hindering electrolyte penetration and increasing cell resistance.

Method used

A method involving coating conductive materials on active materials and spraying binders while stirring with specific blade configurations to form granules with controlled porosity and uniform distribution of components.

Benefits of technology

Enhances electrolyte penetration and improves aggregation of active materials, reducing cell resistance and enhancing battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502845000001_ABST
    Figure 2025502845000001_ABST
Patent Text Reader

Abstract

Provided is a method for producing granules for electrodes of an all-solid-state battery, the method including the steps of (1) coating an active material with a conductive material, and (2) spraying a binder onto the coated active material to produce granules, and an all-solid-state battery using the granules produced thereby.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0033208 filed on March 17, 2022 and Korean Patent Application No. 10-2023-0034278 filed on March 16, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to a method for producing granules for an all-solid-state battery electrode and an electrode for an all-solid-state battery. Specifically, the present invention relates to a method for producing granules for an all-solid-state battery electrode, which prevents components in the granule particles from migrating to the outside and improves the porosity of the granule particles, and an electrode for an all-solid-state battery including the granules produced thereby. [Background technology]

[0003] Currently, various batteries capable of overcoming the limitations of lithium secondary batteries are being researched from the standpoints of battery capacity, safety, output, large size, and ultra-compactness.

[0004] Representative examples of batteries that are being continuously researched in academia and industry include metal-air batteries, which have a much larger theoretical capacity than lithium secondary batteries, all-solid-state batteries, which are safe and do not pose a risk of explosion, supercapacitors, which are large-scale batteries such as NaS batteries or RFBs (redox flow batteries), and thin film batteries, which are ultra-compact.

[0005] Among these, all-solid-state batteries refer to batteries in which the liquid electrolyte used in conventional lithium secondary batteries is replaced with a solid, and since no flammable solvent is used in the battery, there is absolutely no risk of fire or explosion caused by the decomposition reaction of conventional electrolytes, greatly improving safety. In addition, since Li metal or Li alloy can be used as the anode material, there is an advantage in that the energy density relative to the mass and volume of the battery can be dramatically improved.

[0006] In particular, inorganic solid electrolytes in solid-state batteries can be divided into sulfide-based and oxide-based solid electrolytes. Currently, the solid electrolyte that has undergone the most technological development is the sulfide-based solid electrolyte, and materials have been developed that have an ionic conductivity close to that of organic electrolytes.

[0007] Unlike conventional lithium secondary batteries that use liquid electrolytes, the all-solid-state battery uses a solid electrolyte, which means that the solid electrolyte cannot easily penetrate into the pores of the electrodes, which can lead to problems such as physical contact.To solve this problem, a method has been studied in which granules containing an active material are manufactured, pores are formed outside the granules, and then a liquid solid electrolyte is first injected into the pores and then solidified.

[0008] The granules refer to particles consisting of an active material, a conductive material, and a binder. The granules are laminated on an electrode current collector and heat and pressure are applied (sheeting) to manufacture an electrode.

[0009] However, the granules are manufactured by finely spraying the active material, conductive material, and binder in a slurry form and then drying. According to this conventional technology, the binder migrates to the outside of the granules during drying, resulting in granule particles with dense surfaces, which makes it difficult for the electrolyte to penetrate into the granules, resulting in an increase in cell resistance. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2009-289601 A Summary of the Invention [Problem to be solved by the invention]

[0011] The present inventors have completed the present invention as a result of studying a method for preventing the migration of a binder contained in a granule and improving the porosity of the surface of a granule containing an active material in the manufacture of an electrode for an all-solid-state battery.

[0012] The present invention aims to provide a method for producing granules for electrodes of all-solid-state batteries, which can produce granules that grow stepwise by an injected binder, prevent the binder contained in the granules from moving, and improve the porosity of the surface of the granules containing an active material. [Means for solving the problem]

[0013] According to a first aspect of the present invention, (1) coating an active material with a conductive material; and (2) spraying a binder onto the coated active material to produce granules.

[0014] In one embodiment of the present invention, the step (1) may involve mixing the active material and the conductive material in a mixing vessel in which a blade rotates at a peripheral speed of 20 m / s to 100 m / s.

[0015] In one embodiment of the present invention, the step (2) may be performed in a vessel having a main blade at the bottom for stirring the active material and a sub-blade at the side for pulverizing aggregated active material particles.

[0016] In one embodiment of the present invention, the main blades can rotate at a speed of 100 rpm to 300 rpm.

[0017] In one embodiment of the present invention, the sub-blade can rotate at a speed of 1000 rpm to 3000 rpm.

[0018] In one embodiment of the present invention, the granules may be spherical particles having a diameter of 30 μm to 1000 μm.

[0019] In one embodiment of the present invention, the granules may have a porosity of 10% to 50%.

[0020] In one embodiment of the present invention, the binder may be selected from the group consisting of acrylic binders, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyimide, polyamide-imide, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated EPDM, styrene-butylene rubber, and fluororubber.

[0021] According to a second aspect of the present invention, An electrode for an all-solid-state battery is provided, which includes granules coated with a sulfide-based solid electrolyte, the granules including an active material, a conductive material, and a binder, and the granules have a porosity of 10% to 50%. In one embodiment of the present invention, the granules may be spherical particles having a diameter of 30 μm to 1000 μm.

[0022] In one embodiment of the present invention, the binder may be selected from the group consisting of acrylic binders, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymers, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyimide, polyamide-imide, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated EPDM, styrene-butylene rubber, and fluororubber.

[0023] According to a third aspect of the present invention, An all-solid-state battery including the all-solid-state battery electrode as a positive electrode or a negative electrode is provided. Effect of the Invention

[0024] The method for producing granules for electrodes of all-solid-state batteries according to an embodiment of the present invention can improve the porosity of the granule surface by suppressing the movement of the binder inside the granules, thereby improving the cohesion of the active material and the solid electrolyte when the granules are applied to electrodes of all-solid-state batteries. [Brief description of the drawings]

[0025] [Figure 1] FIG. 1 is a schematic diagram illustrating an apparatus for producing granules for an electrode of an all-solid-state battery according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a photograph of the electrode granules for an all-solid-state battery according to an embodiment of the present invention taken with a scanning electron microscope (SEM). [Diagram 3] FIG. 3 is a photograph of the electrode granules for an all-solid-state battery according to another embodiment of the present invention taken by an electron microscope (SEM). [Figure 4] FIG. 4 is a photograph of the electrode granules for an all-solid-state battery according to another embodiment of the present invention taken by an electron microscope (SEM). [Diagram 5] FIG. 5 is a photograph of electrode granules for an all-solid-state battery according to an embodiment of the present invention. [Figure 6] FIG. 6 is a photograph of electrode granules for an all-solid-state battery according to another embodiment of the present invention. [Figure 7] FIG. 7 is a photograph of electrode granules for an all-solid-state battery according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The embodiments provided by the present invention can be achieved by the following description. The following description should be understood as describing preferred embodiments of the present invention, and it should be understood that the present invention is not necessarily limited thereto.

[0027] Unless the measurement conditions and methods are specifically described for the physical properties described in this specification, the physical properties are measured according to the measurement conditions and methods commonly used by those of ordinary skill in the art.

[0028] One aspect of the present invention is to provide a method for producing granules for all-solid-state battery electrodes.

[0029] According to one embodiment of the present invention, a method for manufacturing granules for an electrode of an all-solid-state battery includes the steps of (1) coating an active material with a conductive material, and (2) spraying a binder onto the coated active material to manufacture granules.

[0030] First, a method for manufacturing granules for an electrode of an all-solid-state battery includes the step of (1) coating an active material with a conductive material.

[0031] The electrode for an all-solid-state battery according to an embodiment of the present invention may be any one of an anode and a cathode, and more specifically, the electrode for an all-solid-state battery may be a cathode.

[0032] When the electrode is a negative electrode, the electrode active material contained in the granules is not particularly limited as long as it is a material that can be used as a negative electrode active material for a lithium ion secondary battery. For example, the negative electrode active material can be carbon such as non-graphitizable carbon and graphite carbon; Li xFe2O3 (0 ≦ x ≦ 1), Li x WO2 (0 ≦ x ≦ 1), Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, 2, 3 elements of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8) and other metal composite oxides; lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4 and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; titanium oxides; lithium titanium oxides, etc. One or more selected from the above can be used. According to an embodiment of the present invention, the negative electrode active material may contain a carbon-based material and / or Si.

[0033] When the electrode is a positive electrode, the electrode active material contained in the granules is not particularly limited as long as it can be used as a positive electrode active material for a lithium ion secondary battery. For example, a lithium transition metal oxide containing one or more transition metals can be used as the positive electrode active material. According to an embodiment of the present invention, the positive electrode active material is LiCoO2, LiNiO2, LiMnO2, Li2MnO3, LiMn2O4, Li(Ni a Co b Mn c )O2 (0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), LiNi 1-y Co y O2 (0 < y < 1), LiCo 1-y Mn y O2, LiNi 1-y Mn y O2 (0 < y < 1), Li(Ni a Co b Mn c )O4 (0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), LiMn 2-z Ni z O4 (0 < z < 2), LiMn 2-z Co z O4 (0 < z < 2) and combinations thereof.

[0034] The conductive material contained in the granules is not particularly limited as long as it is a material that is located within the granules and can provide conductivity between the active material and the electrolyte. For example, nickel powder, cobalt oxide, titanium oxide, carbon, etc. are used as the conductive material, and the carbon may be any one or more selected from the group consisting of ketjen black, acetylene black, furnace black, graphite, carbon fiber, and fullerene.

[0035] According to an embodiment of the present invention, the method of coating the conductive material on the active material is not particularly limited. As an example, a method of feeding the coating raw material into a container equipped with a blade capable of rotating at a high speed of 50 m / s or more, and then rotating the blade to transmit a strong impact force and shear force to the powder to perform surface treatment can be used.

[0036] Next, the method for manufacturing granules for an all-solid-state battery electrode includes (2) spraying a binder onto the coated active material to manufacture granules.

[0037] According to one embodiment of the present invention, the step (2) may be performed in a vessel equipped with a main blade for stirring the active material and a sub-blade for pulverizing aggregated active material particles. An example of such a vessel is shown in Fig. 1. As shown in Fig. 1, the present invention stirs the active material with a rotating blade in a vessel and air flowing in from the bottom, while finely spraying a binder solution from the top of the vessel, and the sprayed binder allows granules to grow stepwise.

[0038] According to an embodiment of the present invention, the main blade is provided at the bottom of the container as shown in Fig. 1 and can agitate the coated active material. When the coated active material is agitated in this manner, the binder solution is uniformly sprayed onto the active material, and granules can be grown uniformly. The granules thus manufactured have high surface porosity, so that when the granules are included in an electrode, the electrolyte can penetrate into the inside of the granule particles and into the spaces between the particles, improving, for example, the problem of agglomeration of the positive electrode active material and the solid electrolyte.

[0039] For this reason, the main blade may rotate at a speed of 100 rpm to 300 rpm. If the rotation speed is less than 100 rpm, the active material is not stirred sufficiently, resulting in a problem that the binder solution is not uniformly sprayed onto the active material. If the rotation speed is more than 300 rpm, a problem that phase separation occurs.

[0040] According to one embodiment of the present invention, the sub-blade is provided on the side of the container as shown in FIG. 1 and can pulverize aggregated active material particles, thereby producing granules having a uniform particle size.

[0041] For this purpose, the sub-blade may rotate at a speed of 1000 rpm to 3000 rpm. If the rotation speed is less than 1000 rpm, the pulverization effect of the solidified active material is insufficient, resulting in a problem that the particle size of the produced granules is not uniform, whereas if the rotation speed exceeds 3000 rpm, the degree of pulverization may be excessive.

[0042] The granules are spherical particles containing an active material, a conductive material, and a binder. Here, the term "spherical" does not mean a perfect sphere in the strict sense, but is used as a general concept including particles with a round shape. The fine particles of the active material in a powder state are bound together with the conductive material by a binder solution, and grow into particles with a specific range of specifications.

[0043] According to one embodiment of the present invention, the granules are spherical particles having a diameter of 30 μm to 1000 μm. Here, the spherical particles do not mean perfectly spherical particles, so the diameter means the largest value among the distances from any one point on the particle surface to another point on the surface. Specifically, the diameter of the granules may be 30 μm or more, 40 μm or more, 50 μm or more, 60 μm or more, 70 μm or more, 1000 μm or less, 800 μm or less, 600 μm or less, 400 μm or less, 200 μm or less, 150 μm or less, 120 μm or less, or 30 μm to 1000 μm, 40 μm to 600 μm, 70 to 150 μm. If the diameter of the granules is less than the above range, the voids in the granule layer are small, and the amount of liquid solid electrolyte that is permeated between the granules and coated is reduced, which may make it difficult to achieve physical contact between the active material and the solid electrolyte in an all-solid-state battery. If the diameter of the granules is more than the above range, the distance between the surface in contact with the solid electrolyte and the center of the granule may be large, and the active material contained in the granules may not be fully utilized.

[0044] The binder bonds materials in contact with the center and may cause an additional reaction when it comes into contact with the solid electrolyte that has permeated the gap of the electrode. Among solid electrolytes, sulfide-based solid electrolytes have moisture-sensitive properties, such as generating H2S gas when in contact with moisture, so it is preferable to remove moisture as much as possible when forming granules. According to one embodiment of the present invention, the binder is an organic binder. The organic binder refers to a binder that dissolves or disperses in an organic solvent, particularly N-methylpyrrolidone (NMP), and is distinguished from an aqueous binder that uses water as a solvent or dispersion medium. Specifically, the organic binder may be selected from the group consisting of acrylic binders, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyimide, polyamideimide, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butylene rubber, and fluororubber, but is not limited thereto.

[0045] According to one embodiment of the present invention, in the granules, the active material is 85% by weight to 99.8% by weight, specifically 88% by weight to 99.5% by weight, more specifically 90% by weight to 99.3% by weight, the binder is 0.1% by weight to 10% by weight, specifically 0.2% by weight to 8% by weight, more specifically 0.3% by weight to 7% by weight, and the conductive material is 0.1% by weight to 10% by weight, specifically 0.2% by weight to 8% by weight, more specifically 0.3% by weight to 7% by weight. When the contents of the active material, binder, and conductive material are adjusted within the above ranges, it is advantageous to improve the performance of the battery.

[0046] According to one embodiment of the present invention, the granule has a porosity of 10% to 50%. The porosity of the granule means the volume ratio of voids in the granule, and the porosity can be measured, for example, by BET (Brunauer-Emmett-Teller) measurement method or mercury penetration method (Hg porosimeter), but is not limited thereto. Specifically, the porosity of the granule may be 10% or more, 15% or more, 20% or more, or 25% or more, and may be 50% or less, 40% or less, or 30% or less, or may be 10% to 50%, 15% to 40%, or 25% to 30%. If the porosity of the granules is less than this range, it may be difficult for the solid electrolyte to come into intimate contact with the granules, and the improvement in battery performance may not be significant. If the porosity of the granules is more than this range, the amount of active material is reduced compared to the volume of the granules, and it may be difficult to provide an electrode with a high loading of active material, and the improvement in battery performance may not be significant.

[0047] The granules may be manufactured by a method commonly used in the art, and is not particularly limited. When manufacturing the granules, a binder solution is added together with the fine particles of the active material and conductive material in a powder state to grow the particle size of the granules to a specific level. When the solvent dries from the formed granules, the binder and conductive material, which are relatively light in weight, are positioned outside the granules, and the density of the outside of the granules can be increased.

[0048] One aspect of the present invention is to provide an electrode for an all-solid-state battery comprising the produced granules.

[0049] According to one embodiment of the present invention, the electrode for an all-solid-state battery includes granules coated with a sulfide-based solid electrolyte, the granules include an active material, a conductive material, and a binder, and the granules may have a porosity of 10% to 50%.

[0050] According to one embodiment of the present invention, the granules are spherical particles having a diameter of 30 μm to 1000 μm. Here, the spherical particles do not mean perfectly spherical particles, so the diameter means the largest value among the distances from any one point on the particle surface to another point on the surface. Specifically, the diameter of the granules may be 30 μm or more, 40 μm or more, 50 μm or more, 60 μm or more, 70 μm or more, 1000 μm or less, 800 μm or less, 600 μm or less, 400 μm or less, 200 μm or less, 150 μm or less, 120 μm or less, or 30 μm to 1000 μm or less, 40 μm to 600 μm, 70 μm to 150 μm. If the diameter of the granules is less than the above range, there are few voids in the granule layer, and the amount of liquid solid electrolyte that penetrates between the granules and coats them is reduced, which may make it difficult to achieve physical contact between the active material and the solid electrolyte in an all-solid-state battery. If the diameter of the granules is more than the above range, the distance between the surface in contact with the solid electrolyte and the center of the granule becomes large, which may cause the active material contained in the granules to be underutilized.

[0051] According to one embodiment of the present invention, in order to manufacture an electrode for an all-solid-state battery, granules including an active material, a conductive material, and a binder are first coated on a current collector. The composition of the granules is as described above, and the coating amount of the granules can be determined in consideration of the performance and specific application of the battery. According to one embodiment of the present invention, the granules have an energy density of 1 mAh / cm 2 ~6mAh / cm 2The energy density is a value obtained by dividing the theoretical capacity according to the characteristics of the granule material by the area of ​​the current collector facing the granules. Specifically, the energy density according to the amount of granules applied is 1 mAh / cm 2 ~6mAh / cm 2 , 2mAh / cm 2 ~5.5mAh / cm 2 , 3mAh / cm 2 ~5mAh / cm 2 In terms of battery performance, it is preferable to pursue high energy density, but if an excessively large amount of granules is applied, not only will the actual capacity be far below the theoretical capacity, but the battery may also become undesirably excessively thick.

[0052] The binder bonds materials in contact with the center and may cause an additional reaction when it comes into contact with the solid electrolyte that has permeated the gap of the electrode. Among solid electrolytes, sulfide-based solid electrolytes have moisture-sensitive properties, such as generating H2S gas when in contact with moisture, so it is preferable to remove moisture as much as possible when forming granules. According to one embodiment of the present invention, the binder is an organic binder. The organic binder refers to a binder that dissolves or disperses in an organic solvent, particularly N-methylpyrrolidone (NMP), and is distinguished from an aqueous binder that uses water as a solvent or dispersion medium. Specifically, the organic binder may be selected from the group consisting of acrylic binders, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyimide, polyamideimide, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butylene rubber, and fluororubber, but is not limited thereto.

[0053] According to one embodiment of the present invention, in the granules, the active material is 85% by weight to 99.8% by weight, specifically 88% by weight to 99.5% by weight, more specifically 90% by weight to 99.3% by weight, the binder is 0.1% by weight to 10% by weight, specifically 0.2% by weight to 8% by weight, more specifically 0.3% by weight to 7% by weight, and the conductive material is 0.1% by weight to 10% by weight, specifically 0.2% by weight to 8% by weight, more specifically 0.3% by weight to 7% by weight. When the contents of the active material, binder, and conductive material are adjusted within the above ranges, it is advantageous to improve the performance of the battery.

[0054] According to an embodiment of the present invention, in order for the electrode to be applied to an all-solid-state battery, a liquid solid electrolyte may be introduced into the voids of the granule layer and dried to coat the granules with the solid electrolyte. The solid electrolyte may be coated on at least a part or all of the surface of the granule. The solid electrolyte may be a polymer solid electrolyte formed by adding a polymer resin to a solvated lithium salt, or a polymer gel electrolyte in which an organic electrolyte containing an organic solvent and a lithium salt, an ionic liquid, a monomer or an oligomer, etc., is added to a polymer resin. The solid electrolyte may be one or more selected from a polymer solid electrolyte, a sulfide solid electrolyte, and an oxide solid electrolyte, and according to an embodiment of the present invention, the solid electrolyte is a sulfide solid electrolyte. In the all-solid-state electrode, the sulfide solid electrolyte is applied by impregnating a granule layer made of the above-mentioned granules in a sulfide electrolyte and then drying.

[0055] According to one embodiment of the present invention, the lithium salt is an ionizable lithium salt, Li + X - The anion of such a lithium salt is not particularly limited, but can be represented by F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6- , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , (CF3CF2SO2)2N - In one embodiment of the present invention, the sulfide-based solid electrolyte contains sulfur (S) and has ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and may include Li-PS-based glass or Li-PS-based glass ceramics. Non-limiting examples of such sulfide-based solid electrolytes include Li2S-P2S5, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-LiCl-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2O5, Li2S-P2S5-SiS2, Li2S-P2S5-SnS, Li2S-P2S5-Al2S3, Li2S-GeS2, Li2S-GeS2-ZnS, and the like, and one or more of these may be included.

[0056] According to one embodiment of the present invention, the electrode active material layer including granules coated with a sulfide-based solid electrolyte in the electrode for an all-solid-state battery has a thickness of 100 μm to 400 μm. Here, the electrode active material layer means a sheet-like layer applied on the current collector excluding the current collector when the current collector is used in the manufacture of the electrode. Specifically, the thickness of the electrode active material layer may be 100 μm or more, 110 μm or more, 120 μm or more, 130 μm or more, 140 μm or more, 150 μm or more, 400 μm or less, 350 μm or less, 300 μm or less, 280 μm or less, 270 μm or less, 260 μm or less, 250 μm or less, or 100 μm to 400 μm, 120 μm to 300 μm, or 150 μm to 250 μm. If the thickness of the electrode active material layer is less than the above range, the loading amount of the active material is reduced and the improvement in battery performance may not be significant, whereas if the thickness of the electrode active material layer exceeds the above range, the durability of the electrode is reduced and the improvement in battery performance may not be significant.

[0057] According to an embodiment of the present invention, the electrode active material layer including granules coated with a sulfide-based solid electrolyte in the electrode for an all-solid-state battery includes 20 wt% to 40 wt% of the sulfide-based solid electrolyte based on the content of the granules. Specifically, the content of the sulfide-based solid electrolyte may be 20 wt% or more, 21 wt% or more, 22 wt% or more, 23 wt% or more, 24 wt% or more, 25 wt% or more, 40 wt% or less, 39 wt% or less, 38 wt% or less, 37 wt% or less, 36 wt% or less, 35 wt% or less, or 20 wt% to 40 wt%, 22 wt% to 37 wt%, or 25 wt% to 35 wt%. If the content of the sulfide-based solid electrolyte is less than the above range, electron transfer between the electrolyte and the active material in an all-solid-state battery is not easy, and thus the improvement in battery performance may not be significant. If the content of the sulfide-based solid electrolyte is more than the above range, the loading amount of the active material is relatively reduced, and thus the improvement in battery performance may not be significant.

[0058] In one embodiment of the present invention, an all-solid-state battery is provided that includes the above-mentioned all-solid-state battery electrode as a positive electrode and / or a negative electrode. In constructing the all-solid-state battery, in addition to the solid electrolyte contained in the electrode, a separate solid electrolyte layer can be introduced between the positive electrode and the negative electrode, and such a solid electrolyte layer can also function as a separator in a general lithium secondary battery. The above-mentioned electrode can be used together with a liquid electrolyte as a semi-solid-state battery, and in such a case, a separate polymer separator may be further required.

[0059] The polymer separator is interposed between the negative electrode and the positive electrode, and serves to electrically insulate the negative electrode from the positive electrode while allowing lithium ions to pass through. The polymer separator may be any polymer separator membrane used in the field of general all-solid-state batteries, and is not particularly limited.

[0060] In one aspect of the present invention, there is provided a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.

[0061] Specific examples of the device include, but are not limited to, power tools that are powered by electric motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and the like; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.

[0062] Preferred examples are presented below to aid in understanding the present invention. The following examples are provided to facilitate understanding of the present invention, and the present invention is not limited thereto.

[0063] Working Example Example 1 LFP was prepared as the active material and carbon black as the conductive material, and these were mixed at a weight ratio of 94:3 (active material:conductive material). The raw materials were then placed in a horizontal mixing vessel equipped with a rotor, which was rotated at high speed with a blade at a peripheral speed of 50 m / s to transmit strong impact and shear forces to the powder, coating the surface of the active material with the conductive material. As shown in Figure 1, the active material coated with the conductive material was placed in a vessel (1 L) equipped with a main blade at the bottom for mixing the active material and a sub-blade on the side for pulverizing aggregated active material particles. Thereafter, the conductive material-coated active material was stirred (main blade 300 rpm, sub-blade 3000 rpm) while a binder solution with a solid content of 70% made by mixing polyvinylidene fluoride (PVDF) and NMP was sprayed onto the conductive material-coated active material by a spray method at the top of the container to produce granules with a diameter of about 500 μm so as to achieve a weight ratio of 94:3:3 (active material:conductive material:binder).

[0064] Comparative Example 1 LFP as an active material, carbon black as a conductive material, and an aqueous binder were mixed in a weight ratio of 94:3:3 (active material: conductive material: binder) to prepare a slurry, which was then spray-dried to produce granules with a diameter of 60 μm.

[0065] Comparative Example 2 After preparing LFP as an active material and carbon black as a conductive material, they were mixed in a weight ratio of 94:3 (active material:conductive material), and granules were prepared in the same manner as in Example 1, except that a separate coating step was not performed.

[0066] Comparative Example 3 Granules were produced in the same manner as in Example 1, except that a mixing vessel without a main blade was used.

[0067] Comparative Example 4 Granules were produced in the same manner as in Example 1, except that a mixing vessel without a sub-blade was used.

[0068] Experimental example 1: Electrode property evaluation The particles produced in the examples and comparative examples were subjected to the following physical property tests, and the results are shown below.

[0069] (1) Physical properties related to particle characteristics The granules prepared in Example 1 and Comparative Examples 1 and 2 were photographed by a scanning electron microscope (SEM) and are shown in FIGS. 2 to 4.

[0070] FIG. 2 shows the granules prepared in Example 1. It can be seen that the binder contained in the granules is uniformly dispersed inside the active material, and the porosity of the surface of the granules is high. The porosity measured using a mercury porosity analyzer (Micromeritics Autopore) was about 40%.

[0071] Meanwhile, referring to FIG. 3, which shows the photograph of the granules prepared in Comparative Example 1, it can be seen that the conductive material and binder contained in the granules migrated to the outside of the granules, making the surface of the granules dense and reducing the porosity. The porosity measured using a mercury porosity analyzer (Micromeritics' Autopore) was about 8%.

[0072] 4, which shows the granules produced in Comparative Example 2, shows that the granules were produced by mixing the active material and conductive material without coating them with a conductive material and then spraying the binder, which caused phase separation between the active material and conductive material and prevented the formation of uniform particles. In particular, some irregular granules were formed with non-uniform sizes, but most granules were not formed and the raw materials were mixed together in powder form.

[0073] In addition, the granules prepared in Example 1 and Comparative Examples 3 and 4 were photographed and are shown in FIGS.

[0074] FIG. 5 shows the photograph of the granules produced in Example 1, and it can be seen that uniform spherical granules were produced.

[0075] On the other hand, looking at Figure 6, which shows the granules produced in Comparative Example 1, it can be seen that because the binder was sprayed without the main blade rotating, granules were not produced and the powder remained wet with the binder.

[0076] In addition, looking at Figure 7, which shows the photograph of the granules produced in Comparative Example 2, it can be seen that it is difficult to produce granules with a uniform particle size because granules are produced with only the main blade rotating without the sub-blade.

[0077] Experimental example 2: Battery performance evaluation The granules prepared in Example 1 and Comparative Examples 1 to 4 were applied to one side of an aluminum current collector, rolled, impregnated with a sulfide-based electrolyte of LiPSCl, dried and rolled to prepare a positive electrode with a thickness of about 130 μm (the sulfide-based electrolyte was about 20% by weight of the granules). The sulfide-based electrolyte of LiPSCl was compressed to prepare an electrolyte layer with a thickness of 1.5 mm, and this was used with lithium metal with a thickness of 100 μm to prepare a negative electrode.

[0078] The positive and negative electrodes were stacked and compressed to prepare an electrode assembly, which was then placed in a battery case to prepare an all-solid-state battery.

[0079] The prepared batteries were discharged at 0.1 C and 1.0 C to measure the discharge capacity ratio (1.0 C / 0.1 C), and the results are shown in Table 1 below for each prepared granule.

[0080] [Table 1]

[0081] From Table 1, it can be seen that the granules according to Example 1 have improved output characteristics due to reduced resistance compared to the granules according to Comparative Examples 1 to 4.

[0082] Any simple modifications or variations of the present invention are within the scope of the present invention, and the specific scope of protection of the present invention will be made clear by the appended claims.

Claims

1. (1) coating an active material with a conductive material; and (2) spraying a binder onto the coated active material to prepare granules.

2. 2. The method of claim 1, wherein the step (1) comprises mixing the active material and the conductive material in a mixing vessel having a blade rotating at a peripheral speed of 20 m / s to 100 m / s.

3. 2. The method of claim 1, wherein the step (2) is performed in a vessel equipped with a main blade for stirring the active material and a sub-blade for pulverizing aggregated active material particles.

4. The method for producing granules for an all-solid-state battery electrode according to claim 3, wherein the main blade rotates at a speed of 100 rpm to 300 rpm.

5. The method for producing granules for an all-solid-state battery electrode according to claim 3, wherein the sub-blade rotates at a speed of 1000 rpm to 3000 rpm.

6. The method for producing granules for an all-solid-state battery electrode according to claim 1, wherein the granules are spherical particles having a diameter of 30 μm to 1000 μm.

7. The method for producing granules for an all-solid-state battery electrode according to claim 1, wherein the granules have a porosity of 10% to 50%.

8. The method for producing granules for an all-solid-state battery electrode according to any one of claims 1 to 7, wherein the binder is selected from the group consisting of acrylic binders, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymers, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyimide, polyamideimide, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated EPDM, styrene-butylene rubber, and fluororubber.

9. An electrode for an all-solid-state battery comprising granules coated with a sulfide-based solid electrolyte, The granules include an active material, a conductive material, and a binder; The granules have a porosity of 10% to 50%.

10. The electrode for an all-solid-state battery according to claim 9, wherein the granules are spherical particles having a diameter of 30 μm to 1000 μm.

11. 10. The electrode for an all-solid-state battery according to claim 9, wherein the binder is selected from the group consisting of acrylic binders, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymers, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyimide, polyamideimide, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated EPDM, styrene-butylene rubber, and fluororubber.

12. An all-solid-state battery comprising the electrode for an all-solid-state battery according to any one of claims 9 to 11 as a positive electrode or a negative electrode.

Citation Information

Patent Citations

  • Method for evaluating strength of porous body

    JP2001208661A

  • Cathode electrode, manufacturing method thereof and lithium-sulfur battery using the same

    JP2003208894A

  • Electronic plug-in module to be accommodated in module support

    JP2009212513A

  • Material for formation of electrochemical element electrode, its manufacturing method, and electrochemical element electrode

    JP2010092601A

  • Carbon composite lithium titanate, method for producing the same, active material for nonaqueous electrolyte battery, and the nonaqueous electrolyte battery

    JP2012197187A